Could nature turn a hare into a jackalope? - Hume, Sarah (Journal of Interdisciplinary Science Topics, 2022)
The jackalope is a chimera of a hare and antelope found in North American folklore, taking the entirety of hare features with the addition of antelope horns. Biological processes which could naturally give rise to horn like protrusions on a hare were explored, namely cottontail rabbit papilloma virus and cutaneous horns. While these methods may give rise to horn like growths, it is impossible to control their number and location such that a ‘true’ jackalope appearance i.e., two horns on the top of the head, is achieved.